Antioxidant, Anti-Inflammatory, and Cytotoxic Activities of Garcinia nervosa (Clusiaceae). (11th November 2012) - Seruji, N. M. U.; Khong, H. Y.; Kutoi, C. J.
Abstract : In our continuing interest on Sarawak Garcinia species, we carried out the evaluation of antioxidant, anti-inflammatory and cytotoxic activities on the methanolic extracts of Garcinia nervosa . The extracts were prepared from its air-dried grounded leaves and barks. The evaluation of antioxidant activities was done using the (2, 2-diphenyl-1-picrylhydrazyl) DPPH radical scavenging assay and the result showed high radical scavenging activities. Meanwhile, the anti-inflammatory evaluation was performed using the lipoxygenase assay, hyaluronidase assay, and xanthine oxidase assay which showed, both of these extracts exhibited high anti-inflammatory properties. The lipoxygenase assay showed a high inhibition of enzyme activity for the barks extracts and a moderate enzyme activity for the leaves extracts. However, there were low inhibitions for both extracts in the hyaluronidase assay and only the barks extracts exhibited moderate antigout properties in the xanthine oxidase assay. For the cytotoxic assay, the extracts exhibited positive responses against the three cancer cell lines, the HeLa cell lines, MCF-7 cell lines, and HT-29 cell lines. Thus, Garcinia nervosa contains high antioxidativeand anti-inflammation properties, which have great potential in the development of pharmaceutical and dermatological products.